SENIOR HIGH SCHOOL STUDENTS' ANXIETY IN ENGLISH SPEAKING CLASS(A DESCRIPTIVE STUDY OF LANGUAGE ANXIETY AT SMA LABORATORIUM (PERCONTOHAN) UPI BANDUNG) - Devi Ariani, - (2009)
This paper entitled "Senior High School Students' Anxiety in English Speaking Class: A Descriptive Study of Language Anxiety at SMA Laboratorium (Percontohan) UPI Bandung". The purposes of this study were to find out about the level of anxiety perceived by most of the students, the causes of anxiety felt by the students, and the strategies used by the students to reduce their own anxiety. A descriptive method is used in gaining the data of this study. An adapted questionnaire of Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz, and Cope (1991) is administered to 30 students of a conversation class in a school in Bandung. Besides, an open ended questionnaire and a classroom observation were used to add the data about the causes of anxiety and the strategies used by the students. The results showed that most of the students were 'mildly anxious' (40%) in English speaking class. Besides, there were five 'very anxious' students (16.67%), six 'anxious' students (20%), six 'relaxed' students (20%) and just one 'very relaxed' student (3.33%). The causes of anxiety came from themselves, such as their low proficiency and their confidence, and their surrounding, such as their teacher and classmates behavior. The strategies used by them was then categorized as the strategies mentioned by Kondo and Yang (2004): 'preparation', 'relaxation', 'positive thinking', 'peer seeking', and 'resignation'. Findings show that most of them used 'relaxation strategies'. It is understandable since it reduced their tension when having the lesson.